Aspectos metodológicos da utilização de Data Mining no âmbito da Geografia - Bação, Fernando Lucas; Painho, Marco (Finisterra, 2003)
METHODOLOGICAL ASPECTS OF USING DATA MINING IN GEOGRAPHICAL WORKS. At the start of the new century, geography finds itself in a very interesting position. After various developments made towards the end of the twentieth century mainly due to the rapid progress in the field of computation, geographers now face a new challenge: geospatial data mining. Geospatial data mining could be the key with which geography achieves the scientific objectives at the basis of the quantitative revolution. It is true that most of the opportunities that have enabled geography to grow have originated outside the discipline; it is also true that geographers have always had the intelligence and vision to rapidly adopt those innovations in the practical work of their profession. The quantitative revolution and Geographical Information Systems are important steps in the search for knowledge about space and spatial-temporal patterns, which are of enormous complexity.A new generation of tools has emerged and grown indispensable to anyone concerned with mastering complexity in any field of knowledge. These tools make use of the huge resources and dimension of today’s databases and have ever-growing processing power as their main ally in establishing an inductive approach capable of solving problems far beyond the reach of theoretical formulations. Nevertheless, in order for these tools to contribute to the essential theoretical development of geography, it is necessary to adopt an appropriate methodological framework and escape pure inductive logic. Accordingly, a Popperian epistemological framework is proposed, in which the conjectural activity of the researcher is the core of the scientific work.